Implementation of the 2013 Curriculum in Primary School 55/1 Sridadi Muara Bulian - Samsah, Nur (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2020)
This research aims to describe learning planning, learning implementation, learning assessment that teachers encounter in implementing the 2013 Curriculum in class IV Primary School 55/I Sridadi. This research uses a descriptive qualitative research type because the researcher wants to describe a phenomenon according to the conditions actually experienced by the research subject. The data collected is data regarding the implementation of the 2013 curriculum which includes planning, implementation and assessment of learning activities based on the 2013 Curriculum and this data is presented in the form of words. The data collection techniques used observation, interviews and documentation. Data analysis through data reduction, data presentation, and drawing conclusions. The data validity checking technique uses triangulation. The research results show that the teacher's steps in preparing the Study plan are choosing a theme, reviewing the teacher's book, reviewing the syllabus, then preparing the Study plan. Based on the research results, it can be concluded that the implementation of the 2013 curriculum in class IVA has been carried out well. The implementation of the 2013 curriculum in class IVA received support from class IVA teachers who had taken part in the 2013 curriculum training, the government which helped with teacher and student handbooks, schools which provided Information Technology and Technology facilities. However, there is a lack of student understanding of the learning material.